MODEL LANSKAP PERMAKULTURA KEBUN PERCOBAAN CIKABAYAN UNTUK MEMENUHI KEBUTUHAN PANGAN BERGIZI MAHASISWA ASRAMA IPB - Rizka Nabilah; Wahju Qamara Mugnisjah; Andi Gunawan (http://arl.faperta.ipb.ac.id/, 2017)
The food quality is determined by the food system, from the food production process, food distribution to food consumption. The production process is related to the agricultural landscape planning. That is the most important step to contribute the production results. Yet, basic knowledge about its benefits values for increasing the potential production are unknown, hence people usually ignore this step planning. Bogor Agricultural University (IPB) as the center of excellence of agricultural science and technology can be a potential sample for application of agricultural planning for production. Thus, the concept of permaculture, which is linked by agricultural productivity based on socio-economic, and ecological has a big chance to be applied. The general objectives of this research were to compose permaculture landscape model and for supply nutritious food needs IPB’s dormitory students. The research surveyed bio-physics potency in Cikabayan campus experimental sites. These estimations are really useful for site analysis of model of permaculture. Result showed the nutritious food needs ingredients for IPB’s dormitory students is 2 299.14 tons from source of plant foods and 406.35 tons from source of animal food which is divided into 18 commodities. The results of agricultural planning with the permaculture landscape model at Cikabayan experimental sites. Results showed that there is a potential production corn 28.43 tons, spinach 10.89 tons, tomato 22.348 tons, kale 6.54 tons, bean 16.44 tons, celery 3.92 tons,and spring onion 5.6 tons. Totally production to supply food needs plant about 94.168 tons. These productions results from Cikabayan experimental sites can supply about food needs plant resources 4.09% for IPB’s dormitory students. This approach could be used by local campus institution to created food self-sufficiency from the assets of land.